Digital Consumption Behavior Among College Students: The Role of Online Shopping Frequency and Sharia Financial Behavior in Medan - Sabrina Faraditha; Isnaini Harahap; Purnama Ramadani Silalahi (Jurnal Investasi Islam, 2026)
The development of digital technology has encouraged an increase in online shopping activities among students and has the potential to foster a consumptive lifestyle. From the perspective of Islamic economics, consumption behavior should be based on the principles of balance, prudence, and avoidance of excessive behavior. This study aims to analyze the influence of online shopping intensity and Islamic financial behavior on the consumptive lifestyle of students in Medan City. The research method employed is a quantitative approach using multiple linear regression analysis. Data was collected through the distribution of questionnaires to 400 active undergraduate (S1) students residing in Medan City, with a sample size determined using the Slovin formula at a 5 percent margin of error. The results of the study indicate that the intensity of online shopping has a positive and significant effect on students’ consumptive lifestyles. Additionally, Islamic financial behavior has also been proven to have a significant effect on consumption lifestyles. Together, the two independent variables were able to explain 65.5 percent of the variation in students’ consumption lifestyles. These findings indicate that the high intensity of online shopping can reinforce the tendency toward overconsumption, while Islamic financial behavior has not fully functioned as a consumption regulator amidst a strong digital culture. This research makes an empirical contribution to the development of Islamic economic literature by emphasizing the importance of strengthening the internalization of contextual and applicable Islamic financial values in addressing the challenges of consumption behavior in the digital era.